Antiplatelet and anticoagulation therapy during percutaneous coronary interventions: A review for the interventionalist. (19th June 2018) - Basman, Craig; Tariq, Afnan; Parmar, Yuvrajsinh J.; Asti, Deepak; Coplan, Neil L.; Singh, Varinder P.; Reimers, Carl D.
Abstract : Pharmacotherapy for percutaneous coronary interventions is essential to optimize the balance between thrombosis and bleeding. Currently, choices abound for the selection of antiplatelet and anticoagulation therapies during percutaneous intervention (PCI). This review article discusses the mechanisms, pharmacokinetics/dynamics, and clinical data behind the various pharmacotherapies including; aspirin, thienopyridines, glycoprotein IIb/IIIa inhibitors, vorapaxar, heparin, direct thrombin inhibitors, and factor Xa inhibitors.